Static Equivalent Seismic Analysis of Omo Sebua Traditional Timber Houses in Nias, Indonesia - Pranata, Yosafat Aji; Tani Frisda; Heri Lumban Tobing (International Journal of Integrated Engineering, 2026)
Wooden houses located on Nias Island generally have not experienced damage to structural components when earthquakes have occurred in recent years. The purpose of this study is to conduct a static analysis of the existing Omo Sebua wooden house building located in South Nias, Indonesia. This study uses a three-dimensional structural analysis method with lateral loads modeled using the static equivalent method. Elastic moduli data of the main structural members were obtained from testing on the existing buildings. The research scope is limited to the structural analysis of buildings located in Botohilitano Village and Bawomataluo Village. The design earthquake load is calculated using the equivalent static analysis method. The design acceleration spectral response parameters use data according to the location of the building. The results of the analysis show that the drift that occurs in the building due to earthquake loads does not exceed the permit limits set by SNI 1726:2019. Drift limits range from 0.0014 to 0.0053, while deformation percentages obtained from analysis range from 14.3% to 52.9%, lower than the permitted limit. The ratio of bending moment of the main column to capacity ranges from 0.689 to 0.755, and the axial compression force ranges from 0.019 to 0.201. The ratio of bending moments of the main beam to capacity ranges from 0.204 to 0.375, and shear forces range from 0.056 to 0.099. The column and beam capacity can withstand the maximum factored load. The wooden columns resting on rocks also contribute to reducing the magnitude of earthquake load.